2021
DOI: 10.35580/lageografia.v19i2.15345
|View full text |Cite
|
Sign up to set email alerts
|

Kajian Daerah Sulit Air di Kabupaten Kulon Progo Daerah Istimewa Yogyakarta

Abstract: Water-scarce areas can be identified from geology, meteorology, water installations, and drought conditions in the area. All of these aspects can be found in Kulon Progo Regency. The aim of this research is to identify water scarcity areas in Kulon Progo Regency and to determine priorities areas for building up some deep wells. There are four parts of the method that used in this study, there are water scarcity areas from the geological aspect interpreted based on geological, hydrogeological, and groundwater b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…The runoff coefficient, symbolized as 'C', remains a pivotal hydrological variable, mirroring the proportion of rainfall volume that eventually transforms into the runoff. It's a metric heavily influenced by the terrain's topography, slope, and vegetative cover [13]. Ground-level observations and assessments in the study region revealed a runoff coefficient of 0.6.…”
Section: Deciphering the Runoff Coefficientmentioning
confidence: 96%
“…The runoff coefficient, symbolized as 'C', remains a pivotal hydrological variable, mirroring the proportion of rainfall volume that eventually transforms into the runoff. It's a metric heavily influenced by the terrain's topography, slope, and vegetative cover [13]. Ground-level observations and assessments in the study region revealed a runoff coefficient of 0.6.…”
Section: Deciphering the Runoff Coefficientmentioning
confidence: 96%
“…In the northern part of the basin, this aquifer is composed of lithology which is dominated by sediments resulting from the decomposition of the Sentolo Formation and the Old Andesite, in the form of sandy loam, calcareous clay, tuffaceous sand, slab sand, silt, and lens clay-silt. While in the eastern part of the basin along the Progo River, there are Merapi Muda deposits which are fluviovolcanic deposits, which are composed of coarse sand, gravel sand, and medium to fine sand [12]. Aquifer Group 2 is composed of fine to coarsegrained material, with an average width of 1.5 km and a thickness of up to 40 meters [13] [14].…”
Section: Lithology and Hydrogeology Of The Study Areamentioning
confidence: 99%
“…Beberapa faktor, termasuk geologi, kekeringan dan ketersediaan jaringan air minum, memainkan peran penting dalam mempengaruhi daerah kekurangan air. Untuk itu, tindakan pencegahan bencana juga diperlukan (Hendrayana & Ramadhika, 2016;Rijal et al, 2021). Kajian kapasitas bencana skala rumah tangga sangatlah penting dalam penanggulangan bencana karena mampu memberikan informasi berapa jumlah manusia yang membutuhkan bantuan secara detail yang mana ini sulit diakomodir oleh kajian skala desa maupun kecamatan yang unit analisisnya berupa batas administrasi.…”
Section: Pembahasanunclassified